Safety Standard To Execute The Reinforced Concrete Structures By Using Slipform System (Journal of University of Babylon for Engineering Sciences, 2021)
The development that took part by the early twentieth century in the field of civil engineering, especially concrete construction, was accompanied by extensive progress in the implementation of high-rise building units.Slipform system is the latest executive method that offers the property of greatly reducing construction time compared to other methods by adopting automatic sliding of the total slipform and enabling continuous work 24 hours.The purpose of this research is to achieve the proactive, organizational and preventive procedures (within scientific and applied frameworks) to implement reinforced concrete structures using the slipform system which insures the possibility and high ability to carry out the work properly.The safe standards in the slipform system  are applied through the method of  installation of the slipform, pre-work test procedures, the homogeneity of the distribution of the used loads, continuous checking and monitoring of the slipform movement during operation and maintaining its balance, in addition, the appropriate method for using casting concrete and preliminary tests of concrete retarder additives, maintaining the concrete cover during pouring and the movement of  the slipform and avoiding concrete sticking to the slipform are considered.  These important steps and proper procedures in the implementation work are guarantee of the success of the work.